Marginalised, patronised and instrumentalised: Polish female fans in the ultras' narratives. (February 2020) - Antonowicz, Dominik; Jakubowska, Honorata; Kossakowski, Radosław
Since the 1990s there has been a growing number of female supporters following football clubs and there is little doubt that they have recently become an important part of the audience for both football authorities and clubs. The process of football's feminisation is neither simple nor is it taking place in a social vacuum, and female fans are encountering well-institutionalised football fandom culture, which is deeply entrenched in stadium rituals. This paper offers an empirical study of roles assigned to women in football fandom culture and the way in which this has been done in order reproduce a "traditional" social order on the Polish football stands. In doing so, it examines the grass-roots ultras' magazine To My Kibice (We are the fans) that belongs to an increasingly popular type of fan magazine, which was developed from popular homemade football fanzines in the 1980s. The analyses provide evidence that female supporters are either marginalised (not being counted as regular fans), patronised or instrumentalised by their male peers. These strategies are visible both in language and in the social contexts in which women on the stands are described.